Fatty Acid Profiles of Venus Clam (Marcia opima) and Blood Cockles (Anadara granosa) Harvested at Different Geographical Locations in the Northwest Coast of Sri Lanka - Sethukali, A.; Darshaka Jayasena, D. (Taylor & Francis, 2022)
The present study elucidated the effects of species and geographical location on the fatty acid profile and lipid indices of bivalves. Lipid profiles of venus clam (Marcia opima) and blood cockles (Anadara granosa) harvested from Naruvilikulam and Achchankulam situated on the northwest coast of Sri Lanka were determined, and lipid indices were calculated. The dominant fatty acid group found in bivalves was saturated fatty acids. Total n-3 and n-6 fatty acid contents were similar between the two species. Both bivalve species were identified as potential sources of docosahexaenoic acid. Bivalves from Naruvilikulam site had significantly abundant levels of linolenic and eicosapentaenoic acids (0.83% and 5.69%, respectively). Thrombogenicity index was not influenced by species and geographical location of bivalves. M. opima and bivalves from Naruvilikulam site were detected with lower atherogenicity indices and higher hypocholesterolemic/hypercholesterole-mic ratios than their counterparts and, therefore, can be recommended for consumers interested in healthy food selection.
Keywords: Polyunsaturated fatty acids; Bivalves; Atherogenicity index; Thrombogenicity index; Hypercholesterolemic